The Influence of Cafe Design and Price on Purchase Decision and Customer Satisfaction in Bukit Raya District, Pekanbaru - Ananda, Rizky; Kurniawati, Devi (Indonesian Journal of Economics, Social, and Humanities, 2025)
This study aims to examine the influence of cafe design and price on purchase decision and customer satisfaction among cafe visitors in Bukit Raya District, Pekanbaru. Using a quantitative approach with a sample of 180 respondents, data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results show that both design and price have significant effects on purchase decisions and customer satisfaction. Moreover, purchase decision partially mediates the relationship between design, price, and satisfaction. The findings provide practical insights for cafe managers to enhance customer experience through strategic interior design and pricing policies.